Need-Supportive Professional Development in Elementary School Physical Education: Effects of a Cluster-Randomized Control Trial on Teachers' Motivating Style and Student Physical Activity - Escriva-Boulley, G.; Tessier, D.; Ntoumanis, Nikos; Sarrazin, P. (American Psychological Association, 2018)
This cluster-randomized controlled trial investigated the efficacy of a teacher professional development (TPD) program, grounded on self-determination theory, to increase elementary school teachers' need-supportive motivating style and consequently their students' physical activity (PA) during physical education (PE) lessons. Participants were 15 elementary school teachers and their 293 students. Teachers in the treatment condition received a sports-related notebook and attended four 3-hr workshops over 1 school year; teachers in the control condition received only the notebook. Students' PA and teachers' motivating style were assessed on four occasions via accelerometers and observations, respectively. Results showed that teachers in the treatment condition increased support of their students' psychological needs for the majority of the school year, but there was a slight decrease in the fourth wave of measurement. Students in the treatment condition increased their time spent in moderate-to-vigorous PA (MVPA), independently of the sport taught, whereas their counterparts from the control condition decreased their MVPA. This is the first study to provide elementary school teachers with a PE teacher professional development program grounded in self-determination theory and demonstrate the potential of such a program to improve teachers' motivating style and student MVPA in PE.